Nanotomography of Cell Surfaces with Evanescent Fields. (5th June 2008) - Wagner, Michael; Weber, Petra; Strauss, Wolfgang S. L.; Lassalle, Henri-Pierre; Schneckenburger, Herbert
Abstract : The technique of variable-angle total internal reflection fluorescence microscopy (TIRFM) and its application to nanotomography of cell surfaces are described. Present applications include (1) 3D imaging of chromosomes in their metaphase to demonstrate axial resolution in the nanometre range, (2) measurements of cell-substrate topology, which upon cholesterol depletion shows some loosening of cell-substrate contacts, and (3) measurements of cell topology upon photodynamic therapy (PDT), which demonstrate cell swelling and maintenance of focal contacts. The potential of the method for in vitro diagnostics, but also some requirements and limitations are discussed.